2018
DOI: 10.29313/mimbar.v34i2.3921
|View full text |Cite
|
Sign up to set email alerts
|

Open Unemployment in The Province of Bali

Abstract: The high level of open unemployment in the districts/cities of Bali Province is not in line with the high minimum wage applied and the lower level of labor force participation. This study aims to analyze both the short and long term district minimum wages (UMK), gross regional domestic product (GRDP), labor force participation rates (LFPR) and education on open unemployment in all districts/cities of Bali Province for the period of 2006 to 2017. This study uses error correction model (ECM) analysis techniques.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
1
1
0
1
Order By: Relevance
“…In the problem of unemployment in Gorontalo Province, several socioeconomic indicators affect unemployment, including population growth, economic growth, inflation, and the human development index. Several previous studies have also shown similar findings, where factors such as the human development index (Sumaryoto et al, 2020), inflation (Idris, 2021), population growth (Ayuningtyas, 2019) (Hjazeen et al, 2021), regional minimum wage (Rustariyuni et al, 2018) (Sari & Bangun, 2019) (Parulian & Mahendra, 2021) and economic growth (Prawira, 2018), (Johan et al, 2016) affect the unemployment rate. Previous research studies have found different results and perspectives.…”
Section: Introductionsupporting
confidence: 55%
“…In the problem of unemployment in Gorontalo Province, several socioeconomic indicators affect unemployment, including population growth, economic growth, inflation, and the human development index. Several previous studies have also shown similar findings, where factors such as the human development index (Sumaryoto et al, 2020), inflation (Idris, 2021), population growth (Ayuningtyas, 2019) (Hjazeen et al, 2021), regional minimum wage (Rustariyuni et al, 2018) (Sari & Bangun, 2019) (Parulian & Mahendra, 2021) and economic growth (Prawira, 2018), (Johan et al, 2016) affect the unemployment rate. Previous research studies have found different results and perspectives.…”
Section: Introductionsupporting
confidence: 55%
“…The results of research conducted by Kurniawan (2017), Valentine (2018), andParwata, Suwendra, andYudiaatmaja (2016) show that the minimum wage has a significant negative effect on the unemployment rate. In contrast, Rustariyuni et al (2019), Hajji and Nugroho (2013), Prawira (2018), Sa'adah and Ardyan (2016), Piwulang (2018), Pamungkas (2016) and Georgiadis, Kaplanis, and Monastiriotis (2020) find that wage levels have a positive and significant effect on the level of unemployment.…”
Section: Introductionmentioning
confidence: 96%
“…One of the most important qualities of a person's education is his ability to learn, as well as his competence, skills, and professionalism. The study of character is one of the most essential investments a person may make to improve his quality of life [9]. From this we can conclude that the more educated you are, the more likely you are to get opportunities and jobs.…”
Section: Impact Of Education On Unemploymentmentioning
confidence: 94%